A new analytical method based on pressure transient analysis to estimate carbon storage capacity of depleted shales: A case study. (November 2015) - Chen, Zhiming; Liao, Xinwei; Zhao, Xiaoliang; Feng, Xiaoxu; Zang, Jiali; He, Liping
Highlights: For CO2 geological sequestrations, only a few are interested in depleted shales. Existing methods for evaluating CO2 storage capacity in shales have some disadvantages. Based on pressure transient analysis, a new analytical method is proposed. Method verification is conducted and influences of some critical parameters are studied. Quick and reasonable. Abstract: In this paper, based on pressure transient analysis (PTA), a quick and reasonable analytical method for estimating CO2 storage capacity of depleted shales is introduced. Firstly, a CO2 seepage model for an injection well with constant injection rate is proposed in consideration of Knudsen diffusion, gas adsorption, and stress-sensitivity effect of permeability. Then, combined with Laplace transform and Pedrosa's substitution, the seepage model is solved and the transient pressure solutions of the injection well are obtained. At last, with these solutions, CO2 storage capacity can be easily estimated at an arbitrary injection pressure. To verify the proposed approach, a derived case from the New Albany Shale is studied. Furthermore, on the basis of the case, the influences of some critical parameters on CO2 storage capacity are analyzed. The research results demonstrate that there is a good agreement between the proposed method and the numerical method, with the maximum difference smaller than 1.5%. In addition, sensitive analysis shows that CO2 storage capacity increases with the increasing of stress-sensitivity coefficient, adsorption index, Knudsen diffusion coefficient and constrained injection pressure; it decreases with the increasing of storage ratio. It is also found that as constrained injection pressure increases, the effects of the parameters above on the storage capacity become more obvious.